The impact of branding on SME performance - Haque, A. K. M. Ahasanul; Salleh, Masripan; Sulaiman, Mohamed; Othman, Abdul Kadir (2016)
Resource-based view (RBV) theory states that firms that possess valuable, rare, imperfectly imitable and non-substitutable resources have the capacity to create sustained competitive advantage that translates to superior performance. Branding is an intangible asset that fits this criterion. It is the brand that influences consumers’ minds to make buying decision on products and services they need in a competitive environment, the brand makes all the difference that distinctively differentiates the firm’s products and services against the competition. Studies in many countries have pointed that branding matters for small and medium-sized enterprises (SMEs), reinforcing that it is not only applicable to large organizations or public listed companies. In Malaysia, limited studies show indications that branding is relevant and contribute towards company performance. Thus, the motivation is to pursue a study to analyse the effects (relationship) of branding on performance. This study is undertaken to determine the effects of branding on performance of SMEs in Malaysia. Quantitative methodology is being adopted to identify branding factors affecting SME performance. Six factors emerge from factor analysis using SPSS: branding practice, branding management, branding strategies, branding awareness, branding associations and branding media & technologies. Subsequently, multiple regression technique is used to test the hypotheses. The results of multiple regressions support the hypotheses on relationship between branding practices and performance, and branding associations and performance. Thus, branding affects performance of SMEs in Malaysia. Surprisingly however, branding media and technologies have negative relationships with performance, indicating that its deployment contributes to losses by SMEs. This could be due to high cost of acquiring, deploying, and maintaining technologies that are used to promote brand awareness and brand building. This study therefore contributes to the body of knowledge in marketing and strategic management for SMEs. If property implemented, SMEs in Malaysia could enhance their performance and help achieve the GDP target for the coming years. With the introduction of much anticipated Trans-Pacific partnership Agreement (TPPA) and its implementation in the next two years, SMEs in Malaysia will face greater opportunities and challenges. Branding could be the answer to equip the SMEs, and be able to uniquely differentiate their products and services. Further research on the subject is recommended to identify other possible factors or deeper insights that could increase performance of SMEs.